Preoperative evaluation of the feasibility of laparoscopic cholecystectomy - Jovanović Miodrag; Stanković Nebojša; Mirković Darko (Vojnosanitetski Pregled)
Aim. To determine the possibility of preoperative evaluation of the feasibility of laparoscopic cholecystectomy based on the standard preoperative examinations and findings. Methods. During 1997, 100 consecutively operated patients with the diagnosis of chronic calculous cholecystitis were followed up. Sex and age, and the results of blood count, sedimentation rate, ultrasonography (US), and intravenous cholangiography (IVC) were monitored. Based on adhesions, fibrosis in Calot’s triangle and pericholecystitis, surgical interventions were classified as minor and major. Results. Minor operations were performed in 57, and major in 43 patients. Earlier surgical interventions had been carried out in 8 (18.6%) patients from the major surgery group, while 9 (15.79%) patients had undergone minor surgery. Out of 57 patients with minor surgery, IVC verified the contrast medium filling of the gallbladder in 55 (96.49%) of the patients. Tense gallbladder or wall stratification was not revealed by ultrasonography in any of the patients from this group. Out of 43 patients with major surgery, the gallbladder was not filled with the contrast medium during IVC in 34 (79.07%) patients, while the stratified and tense gallbladder was found by US in 2 (4.65%) patients. The mean sedimentation rate was 14.3 in the patients with minor surgery, and 23.5 in major surgery group. Mean WBC in the patients with minor surgery was 7.4 × 109. The patients with major surgery had slightly increased mean value of the white cell count. It was 8.3 × 109. Conclusion. Statistically significant difference (p ≤ 0.05) was found between the variables of the IVC, sedimentation rate, the white blood count, and the earlier operations. No significant difference was found between other analyzed variables.